2015
DOI: 10.3945/ajcn.115.117556
|View full text |Cite
|
Sign up to set email alerts
|

Acute load-dependent effects of oral whey protein on gastric emptying, gut hormone release, glycemia, appetite, and energy intake in healthy men

Abstract: These findings indicate that, in healthy lean men, the rate of gastric emptying of whey protein is independent of load and determines the initial gastrointestinal hormone response. This study was registered at www.anzctr.org.au as 12611000706976.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
56
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 51 publications
8
56
1
Order By: Relevance
“…The incretin hormones GLP‐1 and glucose‐dependent insulinotropic polypeptide (GIP) are known to be stimulated by whey protein and account for the “incretin effect”, the phenomenon by which insulin secretion is augmented when glucose is given enterally when compared to an isoglycaemic intravenous glucose infusion . Whey protein ingestion also increases plasma glucagon concentrations . Conversely, guar gum is associated with decreased plasma concentrations of GLP‐1 and insulin, and neutral effects on glucagon; therefore, the hormone responses to the whey/guar preload would be expected to represent a complex balance of competing influences and, indeed, we observed a postprandial increase in glucagon and decrease in GLP‐1, but no net effect on insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The incretin hormones GLP‐1 and glucose‐dependent insulinotropic polypeptide (GIP) are known to be stimulated by whey protein and account for the “incretin effect”, the phenomenon by which insulin secretion is augmented when glucose is given enterally when compared to an isoglycaemic intravenous glucose infusion . Whey protein ingestion also increases plasma glucagon concentrations . Conversely, guar gum is associated with decreased plasma concentrations of GLP‐1 and insulin, and neutral effects on glucagon; therefore, the hormone responses to the whey/guar preload would be expected to represent a complex balance of competing influences and, indeed, we observed a postprandial increase in glucagon and decrease in GLP‐1, but no net effect on insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 It was suggested that AA and glucagon regulate each other in a feedback loop that involves α-cells and hepatocytes. It is also important to highlight the use of a dose Our results show that providing 15 g of EAA stimulates glucagon production, although the rise overall was not significantly different from baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Whey protein has been shown to have an insulinotropic effect compared with non-dairy proteins [33] in some studies but not all [34]. Whey protein consumed in amounts of 20 g/day before or after a carbohydrate meal stimulated insulin, glucagon-like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP) and delayed gastric emptying resulting in decreased postprandial glycaemia in people with diet-controlled T2DM [35,36]. It appears that 2.8 g whey in milk and yogurt of our dairy/chicken/nuts/wholegrain meal has no effect on postprandial glycemia and insulin secretion and that meat and dairy protein probably have equivalent effects on insulin release.…”
Section: Discussionmentioning
confidence: 99%